2013
DOI: 10.1037/a0032293
|View full text |Cite
|
Sign up to set email alerts
|

Developmental precursors of young school-age children’s hostile attribution bias.

Abstract: This prospective longitudinal study provides evidence of preschool-age precursors of hostile attribution bias in young school-age children, a topic that has received little empirical attention. We examined multiple risk domains, including laboratory and observational assessments of children's social-cognition, general cognitive functioning, effortful control, and peer aggression. Preschoolers (N = 231) with a more advanced theory-of-mind, better emotion understanding, and higher IQ made fewer hostile attributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 61 publications
5
71
1
1
Order By: Relevance
“…It is possible that poor verbal and visuospatial abilities impede problem-solving involved in non-aggressive responding, such as the identification of benign intent. Previous research and the current study indicate that boys’ low IQ is associated with greater antisocial behavior and hostile attributional bias, but not aggressive response generation (Choe et al, 2013; Hyde et al, 2010; Runions & Keating, 2007). Moreover, meta-analytic findings indicate that low general cognitive ability and SIP problems, while interrelated, contribute distinctively to child maladjustment (Orobio de Castro et al, 2002).…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…It is possible that poor verbal and visuospatial abilities impede problem-solving involved in non-aggressive responding, such as the identification of benign intent. Previous research and the current study indicate that boys’ low IQ is associated with greater antisocial behavior and hostile attributional bias, but not aggressive response generation (Choe et al, 2013; Hyde et al, 2010; Runions & Keating, 2007). Moreover, meta-analytic findings indicate that low general cognitive ability and SIP problems, while interrelated, contribute distinctively to child maladjustment (Orobio de Castro et al, 2002).…”
Section: Discussionsupporting
confidence: 40%
“…We also accounted for childhood empathy to capture motivations for moral behavior that inform aggressive behavioral choices and are distinct from cognitive processes highlighted in most SIP studies. Because of its associations with hostile attributional bias and aggression, child IQ also was included as a covariate (Choe, Lane, Grabell, & Olson, 2013; Runions & Keating, 2007). We hypothesized that childhood SIP problems would predict young men’s increased amygdala reactivity to fear and anger faces, while accounting for this diverse group of covariates.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because poor ToM contributes to biases and difficulties in interpreting social cues, which can result in reactive and aggressive behaviors toward others (Dodge & Coie, 1987). For example, in the current sample, Choe, Lane, Grabell, and Olson (2013) found that preschoolers who had low levels of ToM showed more hostile attribution biases at age six.…”
Section: Theory-of-mind (Tom)mentioning
confidence: 49%
“…Indeed, numerous studies have linked lead exposure, even at relatively low levels, not only with lower IQ and poor executive functioning, but also with the subsequent development of aggression and juvenile delinquency (Needleman and Bellinger 2001; Needleman et al 2002). Considering these findings collectively, it is possible that exposure to lead in the neighborhood may contribute to CPs by disrupting cognitive control mechanisms that have theoretically and empirically been linked to the maladaptive processing of social information (Choe et al 2013; Runions and Keating 2007). …”
Section: Discussionmentioning
confidence: 99%